Disaster Preparedness in Special Elementary Schools: An Analysis of Safety Education in Learning Materials - Evi Widowati; Anik Setyo Wahyuningsih; Arum Siwiendrayanti; Risa Anggita Putri; Hanif Satria Febriananda; Aza Putri Anisa; Ayu Fadilah Wahid; Laura Marulia Subroto (Jurnal Penelitian Pendidikan, 2024)
Safety is a human right, on the other hand, many schools in Indonesia are located in disaster-prone areas. Children are the most vulnerable group during disasters or emergencies, especially children with special needs, so the role of the government through schools is very important to protect them and provide them with basic skills to be able to survive in emergencies. The purpose of this study was to determine the description of the safety education content in teaching materials at Special Elementary Schools (SD LB) as an effort to improve the knowledge and abilities of children with special needs in dealing with emergencies. The research method used is descriptive qualitative. The unit of analysis in this study is all teaching materials at SD LB. Data collection techniques in this study were carried out by means of observation, document studies and semi-structured interviews with representatives of the principals of SD LB. Data analysis was carried out qualitatively and quantitatively to describe the percentage of the distribution of safety education content in teaching materials at SD LB. The results of this study show that the content of safety education for children is already included in the teaching materials for special education from grades 1 to 6 in special elementary schools for the blind, deaf, mentally retarded, physically disabled and autism.